Na cidade escravista: territórios negros no espaço urbano de Vitória-ES (1850 – 1876) - Pedrosa, Kaira Bicalho (2023)
The dissertation discusses the concept of black territory based on documentation and narratives from the official history of the city of Vitória (ES), covering a specific territorial physical cut, a time frame between 1850-1876, and considering the dimensions of urban history and ethnic-racial issues. The capital of Espírito Santo state originated in the Brazilian colonial period, with Portuguese occupation starting in the 16th century, therefore resulting from a hierarchical and exclusionary society, dependent on slave labor and structurally supported by the slave economy. The invisibility and forgetfulness of spaces once occupied by the black population of that time standardize hegemonic narratives that persist to this day. The temporal cut studied is due to the year 1850 being marked by significant economic changes in the Province of Espírito Santo State, and the year 1876 by the publication of the Fundo de Emancipação de 1876. The dissertation contemplates a bibliographic review about the understanding of black territory in Brazil, then it addresses social interaction practices of the black population in the daily life of the city of Vitória. It focuses in particular on commercial and service practices in the area during the period under study, in which enslaved and freed blacks worked daily in the city's public spaces, due to the distinct services provided to society at that time. It is noteworthy that the understanding of black territories and territorialities from the interactive perspective linked to the theoretical perspective of micro-history and decolonial thought in line with ethnic-racial issues allows us to identify a plurality of black territories in Vitória-ES, as well as their erasures and reminiscences.